Diathesis in Mandailing Language South Tapanuli - Rahmawati; Nurmahyuni Asrul; Irma Khoirot Daulay (RIRAI Publisher, 2021)
This study examines diathesis in the South Tapanuli Mandailing language using a morphosyntactic approach. The purpose of this research is to describe the form of diathesis and the classification and structure of diathesis in Mandailing language. The method used in this research is descriptive method with qualitative research type. The data of this research is the South Tapanuli Mandailing language unit which contains diathesis. The results of the analysis show that there are four types of diathesis in the South Tapanuli Mandailing language, namely active, passive, reflexive, and reciprocal.